Treatment outcomes of patients with isoniazid resistant tuberculosis under National Tuberculosis Elimination Programme in Ahmedabad city: a retrospective study - Nagar, Jatin G.; Rami, Kiran C.; Patel, Meghna M.; Bhavsar, Kaushal M. (International Journal of Research in Medical Sciences, 2022)
Background: Drug resistance tuberculosis remains major public health problem worldwide. In India, the incidence of any isoniazid-resistant TB is 11.6% in new tuberculosis patients, while in previously treated patients, incidence is 25%. For isoniazid resistant cases management 6-9 months duration of H mono regimen containing rifampicin, pyrazinamide, ethambutol and levofloxacin is available under national tuberculosis elimination programme. We present a retrospective study on outcomes of patients of H mono regime in years 2019 and 2020 in Ahmedabad city. Methods: Retrospectively we collected data about age, sex, co-morbid conditions, resistance level (high/low level isoniazid resistance) and treatment outcome of patients put on H Mono regimen under programme from January 2019 to December 2020 in Ahmedabad city from Ni-kshay, an online web-based portal. Results: We have collected data of 251 patients (147 in 2019, 104 in 2020). Out of 251, 188 were males and 63 females. Out of 251, favourable outcome seen in 57.4% patients and unfavourable outcome seen in 42.6% patients. Favourable outcome was significantly higher among females compared to males. Conclusions: Management of drug resistance tuberculosis according to drug sensitivity helps in better patient outcome. Early diagnosis of drug resistance and its treatment, timely diagnosis of treatment failure and management, better patient compliance and patient education about disease help in decrease in the unfavourable outcome.